Peran Pemerintah Desa Dalam Pendaftaran Tanah: Sebuah Perlindungan Hukum Kepada Pemegang Hak Atas Tanah - Taupiqqurrahman, Taupiqqurrahman; Hadi, Syamsul; Zaifa, Gilang Abi (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2023)
Land registration is one of the efforts to protect the community's ownership rights over the land they possess. In land registration, the primary starting point is the village government, as all origins of land registration must go through the village government. In carrying out its role, the village government often encounters obstacles that disrupt the land registration process. The purpose of this research is to identify the obstacles faced by the village government in its role in land registration and to determine the efforts needed to enhance the village government's role in land registration. The research method used is a normative juridical approach with a focus on legal regulations, supplemented by interview results. The results of the discussion reveal several obstacles experienced by the village government in carrying out its role in land registration. These obstacles include unresolved land ownership disputes, unclear land boundaries, limited human resources at the village level, and the absence of standardized regulations regarding supporting land registration documents. The efforts required to enhance the village government's role in land registration include conducting public awareness campaigns about the importance of land registration, providing training to village government personnel, and establishing standardized documentation for supporting land registration documents